2022
DOI: 10.3389/fsurg.2022.909854
|View full text |Cite
|
Sign up to set email alerts
|

ACSL3 is a potential prognostic biomarker for immune infiltration in clear cell renal cell carcinoma

Abstract: ObjectiveLong-chain acyl-coenzyme A synthases (ACSLs) catalyze the activation of fatty acid and are often dysregulated in malignancies. The purpose of this research was to figure out the ACSL3's prognostic value and mechanism in clear cell renal cell carcinoma (ccRCC).MethodsThe expression of ACSL3 in ccRCC was investigated in this work using data from the GEO, TCGA, Oncomine and HPA databases. The expression differences of ACSL3 in the cell lines were further detected by qPCR and Western blot. GEPIA, MethSurv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Furthermore, renal cancer cell lines had signifcantly reduced levels of mRNA and protein expression. Additionally, this study demonstrated a strong association between ACSL3 and immune-cell infltration, DNA methylation, and clinical stage [42]. According to Zhang et al's research, it is possible to successfully block the migration, invasion, and proliferation of ccRCC cells by overexpressing ACSL3.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, renal cancer cell lines had signifcantly reduced levels of mRNA and protein expression. Additionally, this study demonstrated a strong association between ACSL3 and immune-cell infltration, DNA methylation, and clinical stage [42]. According to Zhang et al's research, it is possible to successfully block the migration, invasion, and proliferation of ccRCC cells by overexpressing ACSL3.…”
Section: Discussionmentioning
confidence: 54%
“…Increased levels of all these enzymes have been suggested to be involved in molecular processes driving cancer growth and progression [ 116 , 117 ]. While a clear view on the relevance of all the ACSL isoforms in RCC is not yet available, it seems that at least ACSL3 could serve as a potential prognostic biomarker for immune infiltration in ccRCC [ 118 ]. Furthermore, ccRCC cells in vitro depend on ACSL3 for lipid droplet formation.…”
Section: Free Fatty Acids In Renal Cancermentioning
confidence: 99%